2018
DOI: 10.1186/s12903-018-0631-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of infant oral mutilation on dental occlusion and oral health-related quality of life among Kenyan adolescents from Maasai Mara

Abstract: BackgroundInfant Oral Mutilation (IOM) includes germectomy and early extraction of primary and permanent incisors and canines, primarily in the lower jaw.The aim of the present study was to examine the prevalence and impact of IOM, involving the removal of mandibular permanent incisors and/or canines, on dental occlusion and Oral Health-Related Quality of Life (OHRQoL) among Kenyan adolescents from Maasai Mara.MethodsIn a cross-sectional study, 284 adolescents (14–18 yrs. of age) participated in an oral examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 26 publications
0
27
1
3
Order By: Relevance
“…The study was conducted in Maasai Mara, more specifically in Mara North Conservancy, Kenya. The study population consisted of 284 Kenyan teenagers (mean age: 15.0; SD 1.1; range 14–18 years) recruited from the four primary and one mixed secondary schools in the Mara North Conservancy, Maasai Mara, Narok County of Kenya, as previously reported by Kemoli and coworkers [ 39 ]. The study population was representative of the Mara North Conservatory of Maasai Mara and consisted of healthy adolescents present at school on the day of the examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was conducted in Maasai Mara, more specifically in Mara North Conservancy, Kenya. The study population consisted of 284 Kenyan teenagers (mean age: 15.0; SD 1.1; range 14–18 years) recruited from the four primary and one mixed secondary schools in the Mara North Conservancy, Maasai Mara, Narok County of Kenya, as previously reported by Kemoli and coworkers [ 39 ]. The study population was representative of the Mara North Conservatory of Maasai Mara and consisted of healthy adolescents present at school on the day of the examination.…”
Section: Methodsmentioning
confidence: 99%
“…Structured questionnaires were used to collect data on age, gender, medical history, and the use of oral hygiene tools according to procedures previously described [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature extraction of these teeth by traditional healers is believed to cure this condition. However, this practice can cause serious permanent damage to the child resulting in missing teeth and destruction of some of the surrounding permanent teeth [53][54][55][56][57]. A 1989 study conducted in Southern Sudan on the prevalence of Ibyinyo among the hospitalized infants found that one deciduous tooth had been removed from all the studied infants (n=90), and most were suffering from dehydration caused by various other abdominal complications [58].…”
Section: Conflict Between Superstition and Medical Or Dental Practicesmentioning
confidence: 99%
“…[ 21 ] In 2018, a study of teenagers from another area of Maasai land showed that 61.1% had had removal of primary canines mandibular central incisors in the form of dental enucleation/mutilation. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%